Mind’s Labyrinth A Study of the Book of Image and Mind: Film, Philosophy and Cognitive Sciences - Hamed Fardar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The article addresses the book of Image and Mind: Film, Philosophy, and Cognitive Sciences compilation by Gregory Currie. The cognitive approach is one of the relatively recent perspectives on narratological and cinematic studies that emerged from the 1980s and sought to examine the mental processes of the audience through objective exploration in the perceptual and cognitive mechanism of mankind. There are few sources in the Persian language in two areas of narratology and cognitive sciences, and existing books on cinematic studies, such as compilation and translation to the cognitive attitude, are scarce, so the translation and publication of such resources is really useful. In this article, after introducing the exterior origin of the book and the brief description of its content, by examining the form and content of the book, while listing the points from the methodology of the author, some of the conclusions and content lines of the book are critically evaluated. Particularly, at the time of printing the original version and translating it into Persian, there have been many changes in the field of cinematic technologies that could revise some of the ideas in the book.